Photos from NRF 6th Open Assembly in Iceland - Hjalti, Hreinsson (Arctic Portal, 2011)
Photos from NRF the 6th Open Assembly in Iceland, held in Hveragerði 3. - 6. September 2011. Please click on the link above to see the pictures. Use of the pictures are freely allowed as long as citation is credited.